The influence of national cultural attributes on locally produced designs: Case study of Malaysian design - Siek, Perline Hwee Ling *; Lee, Cheng Ean Catherine * (The International Academic Forum (IAFOR), 2021)
This paper examines the influence of national cultural attributes on locally produced designs (i.e. comics, animation, commercial advertisements, printed materials and graphics). Drawing from the inconsistent results of past literature on influences of national cultural attributes on design; it is considered an under-researched area of the important role of cultural values on designs, specifically in the Malaysia context, in which cultural differences among different ethnic groups exist. Because of the paucity of research in this area, this study adopted a quantitative research approach with results derived from the content-analysis of 18 Malaysian designs using a visual preference survey by six experts from the design industry in Malaysia. This study incorporates two stages of sample screenings of a visual preference survey with brief interviews; results show that Malaysian designs need to adhere strictly to requirements and specifications set by the Malaysian authorities; incorporation of Islamic values and code of conduct to reflect the racial harmony and national ideology; and some unique characteristics of the respective ethnic groups in Malaysia were not upheld, thus, they gradually disappeared and/or were blended in the designs. The results and discussion from this study extend the literature on Malaysian design and provide practical implications on how local design industries could produce designs which abide by the boundaries of a Malaysian pluralistic society.